RANCANG BANGUN ROBOT PEMADAM API MENGGUNAKAN PENGOLAHAN CITRA DAN FLAME SENSOR - Kusuma, Robert Dwijoyo; Harianto, Harianto; Wibowo, Madha Christian (Journal JCONES, 2013)
Fire accident is a disaster which freekly many people. This accident often happen because environtment problems or human error. This disaster was take hundred soul or more when happen. Police Departement has a note that disaster which happen in Jakarta as Operasi Ketupat Jaya 2012 has increase 50% than Operasi Ketupat in 2011. To anticipate this disasster many people has done a reasearch for robot which can extinguish fire without human in process, so the human accident when extinguish fire can be reduced. As a solution to solve a matter above writer make a flame extinguisher robot with a differents concept. This Robot have a ability to detect fire indoor with webcam integrated in robot body. This webcam have a function to recognize fire object with image processing. This robot integrated with flame sensors for detect the temperature from the flames. Sensor will have output as a voltage when interact with flames. After that actuator as fire extinguisher will terminate that flames.